2016
DOI: 10.1016/j.jue.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A journey home: What drives how long people are homeless?

Abstract: This paper uses survival analysis to model exits over time from two alternative notions of homelessness. We are unique in being able to account for time-invariant, unobserved heterogeneity. We find that duration dependence has an inverted U-shape with exit rates initially increasing (indicating positive duration dependence) and then falling. Like previous researchers, we find results consistent with negative duration dependence in models which ignore unobserved heterogeneity. Exit rates out of homelessness fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…For instance, Journeys Home data based predominately on single individuals reveal that differences in the amounts of statutory income types such as Newstart and the Disability Support Pension (DSP) and the capacity to increase earnings over time through higher educational status increases the likelihood of exiting an episode of homelessness (Cobb-Clark et al 2016). This evidence adds weight to the importance of better understanding the roles of both individual and household incomes in being able to effectively navigate the PRS.…”
Section: Dynamics Of Low Income Housing Access and Affordabilitymentioning
confidence: 99%
“…For instance, Journeys Home data based predominately on single individuals reveal that differences in the amounts of statutory income types such as Newstart and the Disability Support Pension (DSP) and the capacity to increase earnings over time through higher educational status increases the likelihood of exiting an episode of homelessness (Cobb-Clark et al 2016). This evidence adds weight to the importance of better understanding the roles of both individual and household incomes in being able to effectively navigate the PRS.…”
Section: Dynamics Of Low Income Housing Access and Affordabilitymentioning
confidence: 99%
“…Empirically, several studies have found evidence of state dependence in housing problems 5 (Allgood & Warren, 2003;Piliavan et al 1996;Shinn et al, 1998); however, a recent analysis of the JH survey by Cobb-Clark et al (2015) detected no evidence of duration dependence within homelessness spells.…”
Section: Previous Studiesmentioning
confidence: 99%
“…However, they also found that women: were much less likely than men to have suffered multiple episodes of homelessness; had shorter episodes; and were less likely to have unsheltered episodes. Several studies, including Allgood and Warren (2003), Cobb-Clark et al (2016), and Culhane and Kuhn (1998), have also analysed the durations of homelessness episodes and found that women's episodes are shorter than men's.…”
Section: The Incidence Of Women's Homelessnessmentioning
confidence: 99%
“…The antecedents of other experiences of homelessness, such as doubling up, have been assessed using detailed survey data, such as the FFS and JH (Fertig and Reingold 2008, Curtis et al 2013, Cobb-Clark et al 2016). The findings of these studies differ from those assessing the predictors of more conventional types of homelessness.…”
Section: Causes Of Women's Homelessnessmentioning
confidence: 99%